Glycemic status and macronutrient intake as predictors of sleep outcomes: an analysis of NHANES 2007–2020 data - Basiri, Raedeh; Kassem, Megan; Rajanala, Yatisha; Frankenfeld, Cara L. (Frontiers in Nutrition, 2025)
BackgroundEmerging evidence suggests that glycemic status and dietary intake are associated with sleep duration and quality.ObjectiveTo examine associations between glycemic status, diabetes control, macronutrient energy distribution, and sleep outcomes among participants of the National Health and Nutrition Examination Survey (NHANES).MethodsSleep and dietary variables, including sleep duration (short/normal/extended), trouble sleeping, diagnosed sleep disorder, and macronutrient intake, were obtained from the cross-sectional US NHANES 2007–2020. Glycemic status was defined by self-reported diabetes history and measured HbA₁c. Multivariable adjusted multinomial logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for sleep outcomes associated with glycemic status, diabetes control, and macronutrient intake.ResultsIndividuals with diabetes were more likely to have sleep disorders (OR: 1.61; 95% CI: 1.34–1.93) and trouble sleeping (OR: 1.37; 95% CI: 1.23–1.53) compared to those with normoglycemia. They also showed abnormal sleep durations, with 21% higher odds of short sleep (95% CI: 1.08–1.35) and 37% higher odds of extended sleep (95% CI: 1.12–1.66). Among participants with diabetes, maintaining HbA₁c < 6.5% was associated with 27% higher odds of trouble sleeping (95% CI: 1.05–1.54) versus those with 6.5% ≤ HbA₁c < 9.0%. Macronutrient distribution was differently associated with sleep across glycemic statuses. In individuals with diabetes, low protein intake was associated with higher odds of sleep disorder diagnosis (OR: 2.43; 95% CI: 1.06–5.61). A low-carbohydrate, high-fat intake was associated with lower odds of short sleep duration (OR: 0.78; 95% CI: 0.62–0.98). Among individuals with prediabetes, low-protein diets, particularly when combined with high fat intake, were associated with approximately 2- to 3-fold higher odds of extended sleep duration (OR: 2.04; 95% CI: 1.02–4.08; OR: 2.88; 95% CI: 1.30–6.36). In normoglycemic individuals, similar macronutrient energy distribution patterns were associated with both short and long sleep duration, compared with balanced diets.ConclusionThese findings highlight the importance of considering glycemic status and diet in relation to sleep. This study adds to growing evidence that metabolic health and nutrition influence sleep and may guide future interventions to improve sleep through targeted dietary strategies.